The Consumptive Behavior of Sharia Economics Students at UIN K.H. Abdurrahman Wahid Pekalongan Due to Online Shopping with the Principle of Islamic Consumption Quantity - Rosyada, Nisrina; Nabilla, Agnia Azka; Ningrum, Diah Ayu Puspita; Amelia, Hestina (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study examines the consumptive behavior of students in the Sharia Economics Study Program at UIN K.H. Abdurrahman Wahid Pekalongan and its relation to the quantity principle as a potential solution. Using a qualitative method, data were gathered through literature review and interviews with five students experienced in online shopping. Results show that four out of five respondents engaged in consumptive behavior and expressed regret. One respondent, who did not show consumptive habits, observed that those who did eventually regretted it. Through this regret, all five suggested mindful consumption, such as spending based on need and income, avoiding waste, and prioritizing saving.